Sistem Pendukung Keputusan Pemilihan Alat Kontrasepsi untuk Keluarga Berencana dengan Fuzzy Mamdani - Erma Anggi Giwanti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Contraceptives are a tool or method used to regulate the spacing of pregnancies and prevent pregnancy. The use of this contraceptive is expected to reduce the growth rate in the Sumbersari area. The selection of contraceptives is carried out by experts in the field of family planning. In the selection of contraceptives, there are still some acceptors who experience side effects due to the selection of inappropriate contraceptives. The side effects caused include weight gain, menstrual disorders, and hypertension. In overcoming these problems, a decision support system is needed for the selection of contraceptives. In this study, the author will apply the Mamdani fuzzy logic method to create a contraceptive selection system using Matlab software. Data collection in the form of age, number of children, blood pressure and BMI as input variables. Meanwhile, the output variable of the study is contraceptives based on the duration of use with categories of very low (pills), low (injections), moderate (implants), long (IUD), and very long (MOW). The Mamdani fuzzy method consists of four stages, namely fuzzification, implication function, rule composition, and defuzzification. Based on the study, it was found that 86 acceptor data were in accordance with the health center data. The accuracy results of 100 acceptor data at the Sumbersari Health Center obtained a value of 86%.
:: Finalisasi Repositori File 4 Juni 2026_Kurnadi
Keywords: contraception; SPK; fuzzy logic; Mamdani